Galectin-14 Promotes Trophoblast Migration and Invasion by Upregulating the Expression of MMP-9 and N-Cadherin - Wang, Miaomiao; Xu, Yuqing; Wang, Peng; Xu, Yanfei; Jin, Pengzhen; Wu, Zaigui; Qian, Yeqing; Bai, Long; Dong, Minyue (Frontiers in Cell and Developmental Biology, 2021)
Galectin-14 is specifically expressed in placental trophoblast and its expression is reduced in trophoblast retrieved from the cervix of women destined to develop early pregnancy loss. However, the roles of galectin-14 in regulating trophoblast and in the pathogenesis of pregnancy complication has never been investigated. In the current research, we aimed to investigate the roles of galectin-14 in the regulation of trophoblast. Tissues of placenta and villi were collected. Primary trophoblasts and human trophoblast cell line HTR-8/SVneo were used. Western blotting and RT-PCR were used to quantify the gene expression. The siRNA-mediated galectin-14 knockdown and lentivirus-mediated overexpression were performed to manipulate the gene expression in trophoblast. Transwell migration and invasion assays were used to evaluate cell migration and invasion capacity. Gelatin zymography was used to determine the gelatinase activity. Galectin-14 was significantly decreased in the villi of early pregnancy loss and the placenta of pre-eclampsia. Knockdown of galectin-14 in primary trophoblasts inhibited cell migration and invasion, down-regulated the expression of MMP-9 and N-cadherin, the activity of MMP-9 and decreased the phosphorylation of Akt. Meanwhile, the overexpression of galectin-14 in HTR-8/SVneo promoted cell migration and invasion, up-regulated the expression of MMP-9 and N-cadherin, the activity of MMP-9 and increased the phosphorylation of Akt. Increased Akt phosphorylation promoted cell migration and invasion, up-regulated the expression and activity of MMP-9, while decreased Akt phosphorylation inhibited cell migration and invasion, down-regulated the expression and activity of MMP-9. Thus, galectin-14 promotes trophoblast migration and invasion by enhancing the expression of MMP-9 and N-cadherin through Akt phosphorylation. The dysregulation of galectin-14 is involved in the pathogenesis of early pregnancy loss and preeclampsia.